Notes on the Eastern Comma Polygonia c-album agnicula Moore, 1872 (Lepidoptera: Nymphalidae: Nymphalinae) from Tawang District, Arunachal Pradesh, India - Monsoon Jyoti Gogoi; Bharat B. Bhatt; Anupam Sarmah (Journal of Threatened Taxa, 2015)
The Comma, Polygonia c-album ranges across W.Himalaya up to Sikkim-Bhutan but not reported from North East India. Altogether, three subspecies occur within Indian region.This sighting is not surprising as Tawang dist. shares boundary with Bhutan. This sighting shows that more survey is needed in W. Himalaya to know the butterfly fauna of the region.